Modernização da agricultura e reestruturação produtiva da atividade leiteira - Silva, Eliane Regina Francisco da [UNESP] (2015)
The restructuring process involves the introduction of changes in management, production, organization, and the hiring of the workforce in many different sectors of the economy and a global perspective. In the case of dairy farming, this process had passed from production to the final consumer. In Brazil, the productive restructuring, technological, logistical and social terms, has been reaching the national dairy industry from the 1990s, as a result of foreign trade liberalization, the deregulation and monetary stabilization. In Portugal, the change in the dairy scenario begins in the 1990s, when it starts to be introduced into this country the system of production quotas set by the European Union (EU). The goal of the research was to analyze the production and processing of milk in the municipality of Presidente Bernardes, located on Geographic microrregion Presidente Prudente and Entre-Douro and Mondego, located in the Central Region of Portugal. The analysis covered the period between the years 1990 and 2010. The choice of the municipality of Presidente Bernardes for conducting empirical research is due to the fact that the economy of this town is structured in agriculture, with emphasis on livestock activities milk, which is the focus of the work, and cut. The choice of Entre-Douro and Mondego for empirical research in Portugal is correlated with the point that in this region there is a marked regional difference, because the flatter coastal part with more favorable climate, there are better ways to access markets and more accessible, milk production being geographically concentrated. This work was designed as a field study and the methodological procedures were used: literature review and reading of selected material; collection and systematization of secondary data in the Agricultural Census of 1995/6 and 2006 Censuses the IBGE of 1991, 2000 and 2010 and the LUPA Project 1995/6 and 2007/8...